Achalasia Carcinoma Sequence - Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2001)
We report a case of carcinoma of the esophagus in a 58 years old woman with achalasia, who has been diagnosed since 30 years ago, which initiated by surgical treatment (myotomy) and the symptoms recurred since 3 years ago. According to the progress of the disease, malignancy was strongly suspected due to prolonged stasis and mucosal irritation caused by achalasia (achalasia carcinoma sequence). Because of these contributing factors for the development of serious complications such as malignancy, the diagnosis of achalasia must be systematically diagnosed and treated agressively. Surveillance endoscopy in patients with achalasia should be performed every 1-2 years. Key words: achalasia carcinoma sequence, surveillance endoscopy